Influence of composition and method of introduction of the pH regulator on the physico-chemical properties of aluminium hydroxide dispersions formed during water treatment - Zyhmant, Alesia V.; Savitskaya, Tatsiana A.; Hrynshpan, Dzmitry D. (Journal of the Belarusian State University. Chemistry, 2026)
The laser diffraction method was used to study the influence of the various pH regulators and their introduction methods on the physico-chemical properties of aluminium hydroxide dispersions formed from aluminium-containing coagulants during water treatment. It was found that by a one-stage introduction of pH regulators the sedimentation rate of coagulation aggregates increased in the KHCO3 – NaOH – NaClO series from 3.0 ⋅ 10−3 to 5.7 ⋅ 10–3 m/s. Transition to a three-stage introduction in the case of NaOH causes an increase in the sedimentation rate of coagulation aggregates by 1.5 times while in the case of KHCO3 it decreased by 2.1 times. Coagulation aggregates formed in the presence of NaClO are the least sensitive to the introduction method of pH regulators. It is shown that the transition to three-stage introduction of pH regulators increased the growth rate of coagulation aggregates. The obtained results open the possibility of simplifying and reducing the cost of water treatment process.